Komunikasi Perkawinan Nyerod Pada Umat Hindu Di Kota Mataram - Ngakan Made Sadia; I Nyoman Wijana; I Wayan Wirata (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2020)
Marriage is the basic right of every human being to form a complete household with the aim of continuing descendant, in accordance with the constitution number 39 year of 1999 concerning human rights. In marriage ceremonies there are a lot of variety happening in the community based on ethnic with one another in one nation, religion, culture, and social class, which is sometimes clashed with certain religious rules or laws. Marriage is considered valid if it is carried out according to the marriage law of each religion and belief and is recorded by the authorized institution according to the applicable legislation. Thus marriage is a bond in which husband and wife or both people become one entity and become a relationship that is so unique and very exclusive. Marriage is something that has existed for a long time, is very universal and has become a special tradition in human life. There are no differences such as; community, economy and political system. Thus the problem can be formulated as follows: 1) ‘nyerod’ marital communication strategy for the Hindus in Mataram city; 2) Communication process for ‘nyerod’ marriage to the Hindus in Mataram city; and 3) Implications of communication of ‘nyerod’ marriage to the Hindus in Mataram city. This research uses a qualitative approach, data collection techniques are through observation, in-depth interviews, and documentation and data analysis using interpretative descriptive. The results of the study are explained as follows; The Communication Strategy in Nyerod Marriage for the Hindus in Mataram are of two main explanations, namely; 1) Receiving the implementation of specialization for women of the Ksatria dynasty by Wangsa Wesya, getting approval from the old people of the Wesya, and 2) Not accepting the implementation of specialization so that the perpetrator chooses running married by loving each other, to realize his marriage the communication strategy that is applied is to flee to marry without being known by the parents. Communication process in Nyerod marriage to the Hindus in Mataram is through 1) Patiwangi Ceremony: 2) Ngetelunin Ceremony: 3) Ceremony of Mewidi Widhana. The implications of Nyerod Marriage of the Hindus in Mataram is sanctioned either by the families of the perpetrators, the families of the bride and the society.